Deep venous thrombosis related to the pregnancy-puerperal cycle and physiopathological changes with the advent of COVID-19 (Research, Society and Development, 2021)
Objective: Evaluate the main risk factors for Deep Venous Thrombosis (DVT) in pregnant and postpartum patients and whether there is a relationship with COVID-19 with increased cases. Methodology: Systematic literature review, in which searches were performed on the electronic platforms PubMed, LILACS and Scielo, using the descriptors: deep venous thrombosis, pregnancy and COVID-19. Results: The sample resulted in 15 articles. 93.3% of the surveys state that women in the gestational or postpartum period are more likely to develop DVT due to physiological changes during the period, with 26.6% of the total studies showing risk factors for worsening the condition, such as heart disease, pregnancy and age older than 35 years, cesarean delivery, recent surgery, among others. No study reported an increased incidence of DVT cases in pregnant women infected with the SARS-CoV-2 virus, however 20% of the articles demonstrate an increase in the number of complications associated with infection, such as premature birth, abortion and fetal death. Conclusion: There are high risks for thrombotic events in pregnancy, especially in pregnant women with aggravating factors, such as the triggers of Virchow's triad (stasis, hypercoagulation and vascular damage), with the need for special attention to these patients. There is no established association between an increase in DVT cases with COVID-19 infection, and the prophylactic use of Low Molecular Weight Heparin (LMWH) is recommended in these patients, although more studies on the subject are needed due to the short time of disease onset.